The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s10072-017-3223-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender effect on well-being of the oldest old: a survey of nonagenarians living in Tuscany: the Mugello study

Abstract: The population of industrialized nations is progressively aging, with Italy having one of the most elderly populations in the world. Natural aging may be associated with physical and cognitive impairments, often straining public resources. The present study aims to investigate the influence of gender on wellness of the nonagenarians. We evaluated quality of life among nonagenarians living in the Mugello area, an Italian location with a large population of individuals > 90 years, using the Health Survey Scoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…These findings might be explained in terms of a better psychological adaptation to aging and perhaps to the fact that with age comes not only wisdom, but also the attribution of greater meaning or value to life. As concerns the influence of gender, previous studies have reported a poorer HRQoL among women than among men [31,32,33,34,36,37], and our own results corroborate this difference. Thus, women obtained poorer scores in both components of HRQoL, although the association was only significant for the mental component of a very low quality of life.…”
Section: Discussionsupporting
confidence: 89%
“…These findings might be explained in terms of a better psychological adaptation to aging and perhaps to the fact that with age comes not only wisdom, but also the attribution of greater meaning or value to life. As concerns the influence of gender, previous studies have reported a poorer HRQoL among women than among men [31,32,33,34,36,37], and our own results corroborate this difference. Thus, women obtained poorer scores in both components of HRQoL, although the association was only significant for the mental component of a very low quality of life.…”
Section: Discussionsupporting
confidence: 89%
“…Concerning gender differences, our findings supported previous studies, which reported a poorer health-related quality of life among women than among men [48][49][50]. In the present study, male older adults were more often currently employed and living with a spouse than female older adults.…”
Section: Longitudinal Changes In Health-related Quality Of Lifesupporting
confidence: 91%
“…The cross-sectional and longitudinal correlation of PA with mood and cognitive status is also well established (Sofi et al, 2011; Padua et al, 2018; Herr et al, 2016). Again, PA could modify cognitive performance and mood, but on the contrary, appropriate treatment of unaddressed depression and cognitive decline may potentially reflect both on PA and on disability.…”
Section: Discussionmentioning
confidence: 99%